2015
DOI: 10.1111/jpn.12428
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nutriactive phytochemical – gamma‐oryzanol in experimental animal models

Abstract: SummaryGamma-oryzanol (GO) is an abundant dietary antioxidant that is considered to have beneficial effects in cardiovascular disease, cancer and diabetes. Other potential properties of GO include inhibition of gastric acid secretion and decreased post-exercise muscle fatigue. GO is a unique mixture of triterpene alcohol and sterol ferulates present in rice bran oil, a byproduct of rice processing. GO has been studied by many researchers over the last three decades. In particular, the utility of GO supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 65 publications
(96 reference statements)
2
20
0
7
Order By: Relevance
“…γ-Oryzanol has been proven safe for consumption with no major side effect [11,12]. Numerous studies have reported health-beneficial properties of γ-oryzanol including anti-hyperlipidemic, anti-ulcerogenic, anti-carcinogenic, anti-inflammatory, anti-diabetic, and antioxidant effects [10,11]. We recently demonstrated the mechanism by which γ-oryzanol regulates cellular redox homeostasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…γ-Oryzanol has been proven safe for consumption with no major side effect [11,12]. Numerous studies have reported health-beneficial properties of γ-oryzanol including anti-hyperlipidemic, anti-ulcerogenic, anti-carcinogenic, anti-inflammatory, anti-diabetic, and antioxidant effects [10,11]. We recently demonstrated the mechanism by which γ-oryzanol regulates cellular redox homeostasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most of the data available comes from studies in vitro or from animal models. In a recent study, Szcześniak et al revised several of these studies and concluded that beneficial effects of Orz are due to its antioxidant activity and modifications in lipids metabolism [ 11 ]. A remarkable lack of specific dosages have used in animal models (doses range to 1–2000 mg/kg of body weight), or in vitro (doses range to 0.1–1000 µmol) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Szcześniak et al revised several of these studies and concluded that beneficial effects of Orz are due to its antioxidant activity and modifications in lipids metabolism [ 11 ]. A remarkable lack of specific dosages have used in animal models (doses range to 1–2000 mg/kg of body weight), or in vitro (doses range to 0.1–1000 µmol) [ 11 ]. Nevertheless, is still necessary to clarify the exact mechanisms of action and confirm the results obtained in human studies.…”
Section: Introductionmentioning
confidence: 99%
“…Gambogic acid may ameliorate angiogenesis in mice with diabetic retinopathy ( Cui et al, 2018 ). Gamma-oryzanol was shown to be safe and effective in improving the conditions of diabetes mellitus in several animal studies ( Szcześniak et al, 2016 ). Octopamine may be involved in central blood pressure regulation ( Delbarre et al, 1982 ).…”
Section: Resultsmentioning
confidence: 99%